Beyond corticosterone: The acute stress response increases DNA damage in house sparrows. Issue 8 (15th August 2020) - Gormally, Brenna M. G.; Estrada, Rodolfo; McVey, Mitch; Romero, L. Michael
Abstract: Although corticosterone (Cort) has been the predominant metric used to assess acute stress in birds, it does not always accurately reflect how an animal copes with a stressor. Downstream measurements may be more reliable. In the current study, we tested the hypothesis that acute increases in DNA damage could be used to assess stressor exposure. Studies have shown DNA damage increases in response to stress‐related hormones in vitro; however, this has not yet been thoroughly applied in wild animals. We exposed house sparrows ( Passer domesticus ) to a 30‐ or 120‐min restraint stressor and took blood samples at 0, 30, 60, and 120 min to measure Cort, DNA damage, and uric acid. Both treatments increased DNA damage and Cort, and decreased uric acid. It thus appears that DNA damage can reflect acute stressor exposure. To improve the usability of DNA damage as a metric for stress, we also tested the impacts of sample storage on DNA damage. Leaving red blood cells on ice for up to 24 hr, only slightly influenced DNA damage. Freezing blood samples for 1–4 weeks substantially increased DNA damage. These findings emphasize the importance of reducing variation between samples by assaying them together whenever possible. Overall, these results indicate that assessing DNA damage is a valid method of assessing acute stressor exposure that is suitable for both laboratory‐ and field‐based studies; however, additional research is needed on the molecular dynamics of nucleated red blood cells, including whether and how their DNA is repaired. Abstract : Acute restraint stress in house sparrows causes an increase in (a) red blood cell DNA damage and (b) corticosterone (Cort) and a decrease in (c) uric acid. Research Highlights: When house sparrows experience an acute stressor, corticosterone and DNA damage increases while uric acid decreases. This suggests DNA damage as an additional metric of stress. In addition, red blood cell DNA damage is affected by freezing.